Konversi Agama dalam Kehidupan Pernikahan - Rani Dwisaptani; Jenny Lukito Setiawan (Humaniora, 2008)
This research aims to investigate factors and processes underlying religious conversion in marital life. The study adopts a qualitative method. The data were collected from three participants through semi-structured interviews. Results showed that religion conversion by the participants resulted from their desire to marry somebody having a different religion; the feeling of not meeting God in their former religion, which is related to the lack of religious values implanted early in life, and to life crises and conflicts.